PENCAPAIAN HASIL BELAJAR MATEMATIKA SISWA MELALUI PENATAAN KEBIASAAN BELAJAR - Haidir Haidir (Universitas Islam Negeri Sumatera Utara Medan, 2018)
This study aims to reveal the contribution of learning habits to student learning outcomes in the field of mathematics study at Junior High School Istiqlal Deli Tua Medan. This type of research is classified as expost facto where the analysis uses simple correlation and regression. The population is 430 people while the selected sample is 198 students using stratified proportional random sampling technique. The data of learning habit was obtained by compiling the questionnaire having reliability of 0.890., While the learning result data was taken from the value of the raport then standardized using Z score method. The strength of the relationship between learning habits of student learning outcomes mathematics known from the value of correlation coefficient (r2) of 0.51 while the value of coefficient of determination (R2) of 0.26. It turns out that the calculation shows that thitung ≥ ttable or 8.30 ≥ 2.57. Thus it can be stated that the regression equation model is stated significant.Keywords: Learning Habits, Mathematics Learning Outcomes